Layer-by-layer self-assembled zinc ion battery composite diaphragm as well as preparation method and application thereof

The preparation of the reed floc fiber/montmorillonite composite separator through layer-by-layer self-assembly technology has solved the environmental protection and dendrite growth of the aqueous zinc ion battery separator, achieved efficient ion transport and zinc dendrite inhibition, and improved the stability and life of the battery.

CN120565997APending Publication Date: 2025-08-29NANJING INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510680069.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-26
Publication Date
2025-08-29

AI Technical Summary

Technical Problem

The existing aqueous zinc ion battery separators have problems with uncontrollable growth and corrosion of zinc dendrites, and are insufficient environmental protection, resulting in the end of battery life.

Method used

The composite separator is prepared by layer-by-layer self-assembly technology using cheap and environmentally friendly reed floc fibers and montmorillonite. The reed floc fibers/montmorillonite composite layer is deposited layer by layer through electrostatic action to build a uniform porous structure to inhibit the growth of zinc dendrites.

Benefits of technology

The prepared composite separators are cheap, green and environmentally friendly, have excellent ion transport performance and good dendrites' growth effect, improving battery stability and life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120565997A_ABST
    Figure CN120565997A_ABST
Patent Text Reader

Abstract

The invention discloses a layer-by-layer self-assembled zinc ion battery composite diaphragm as well as a preparation method and application thereof, and belongs to the technical field of novel battery energy storage. The layer-by-layer self-assembled zinc ion battery composite diaphragm comprises a self-assembled reed fiber layer and a montmorillonite composite layer. The preparation method comprises the steps of preparation of the reed fiber base membrane, deposition of the positive charge layer and deposition of the negative charge layer. According to the preparation method, cheap and environment-friendly reed flocculus fibers and montmorillonite in nature are selected as basic materials, and the reed flocculus fiber / montmorillonite composite diaphragm which is good in toughness and has a uniform porous structure is prepared by applying an LbL technology. The composite diaphragm is low in price, green and environment-friendly, and has excellent ion transmission performance and a good effect of inhibiting dendritic crystal growth.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for preparing a composite diaphragm, and specifically to a layer-by-layer self-assembled zinc ion battery reed fiber / montmorillonite composite diaphragm, its preparation method, and application, belonging to the field of new battery energy storage technology. Background Art

[0002] The development and application of new, clean, and renewable energy sources are crucial for resolving energy crises and other challenges. Currently, lithium-ion batteries are widely used in portable electronic devices and electric vehicles. However, global lithium resource availability is uneven, costs are high, and lithium-ion batteries themselves present safety and environmental concerns, prompting a continuous search for more competitive and safe alternative energy storage devices.

[0003] Aqueous zinc ion batteries use metallic zinc as the negative electrode, containing Zn 2+ Aqueous solutions as electrolytes offer advantages such as low cost, safety, environmental friendliness, high theoretical capacity (820 mAh g), and low redox potential (0.76 V vs. SHE). They hold great promise for large-scale energy storage and are considered an ideal alternative battery system. Current limitations on the application of aqueous zinc-ion batteries include uncontrolled zinc dendrite growth, corrosion of the zinc anode, and hydrogen evolution reactions.

[0004] During the battery charge and discharge process, due to the uneven distribution of the electric field on the electrode surface, the difference in ion flux or the mismatch between the diffusion rate and deposition rate of zinc ions in the electrolyte, zinc ions will be deposited on the negative electrode of the battery, thereby generating dendrites. Once the dendrites continue to grow and pierce the diaphragm, the battery will short-circuit and end its life. As an important part of the battery system, the diaphragm plays the role of isolating the electrodes, conducting active ions and inhibiting the growth of dendrites. At present, the glass fiber diaphragms commonly used in the industry have rich porosity and good hydrophilicity, but they are not environmentally friendly enough and have uneven pore distribution. They can easily induce uneven deposition of zinc ions on the negative electrode and are easily pierced by growing dendrites, causing battery failure.

[0005] Therefore, there is an urgent need for a low-cost, green and environmentally friendly layer-by-layer self-assembled zinc ion battery composite membrane with excellent ion transport performance and good dendrite growth inhibition effect, as well as a preparation method and application thereof. Summary of the Invention

[0006] To address the shortcomings of existing aqueous zinc-ion battery separators, the present invention provides a layer-by-layer (LbL) self-assembled reed fiber / montmorillonite composite separator for zinc-ion batteries. Specifically, the present invention utilizes naturally inexpensive and environmentally friendly reed fiber and montmorillonite as base materials and employs LbL technology to produce a reed fiber / montmorillonite composite separator with excellent toughness and a uniform porous structure. This composite separator is inexpensive, environmentally friendly, and exhibits excellent ion transport properties and excellent dendrite growth inhibition.

[0007] At the same time, the present invention provides a method for preparing a layer-by-layer self-assembled zinc ion battery composite diaphragm.

[0008] At the same time, the present invention provides an application of a layer-by-layer self-assembled zinc ion battery composite diaphragm in aqueous zinc ion batteries and zinc ion symmetrical batteries.

[0009] In order to solve the above technical problems, the technical solution adopted by the present invention is:

[0010] A method for preparing a layer-by-layer self-assembled zinc ion battery composite diaphragm comprises the following steps:

[0011] 1. Preparation of reed fiber base membrane

[0012] S1, taking 3-10g of cleaned reed fluff, placing it in a 4-8% by mass NaOH, 0.8-1.5% by volume H2O2 aqueous solution system, ultrasonically treating it for 10-20 minutes, then heating it in a water bath at 60-80°C for 2-4 hours to remove lignin, then filtering out seed impurities, washing it with pure water several times, filtering it again, and drying it in an oven at 60-100°C for 12-24 hours to obtain reed fluff fiber;

[0013] S2, placing the reed fluff fiber in a KOH / Na2SO3 mixed solution and hydrothermally reacting it at 120-140°C for 10-15 hours to further remove lignin and hemicellulose;

[0014] Preferably, the concentration of the mixed solution is 2-4 mol·L-1 KOH+0.1-1 mol·L-1 Na2SO3.

[0015] S3, washing the catkin fibers after hydrothermal treatment in S2 with pure water for multiple times, adjusting the pH value of the suspension to neutral, using vacuum filtration technology to filter and form a wet film, placing the wet film between two pieces of glass, and drying it in an oven at 60-100°C for 12-24 hours to obtain a catkin fiber base film with good toughness and a uniform porous structure, and the base film thickness is about 600-1200μm.

[0016] Second, positive charge layer deposition

[0017] S4, soaking the reed fluff fiber-based membrane obtained in S3 in a positively charged polyelectrolyte solution for 3-10 minutes to make its surface positively charged.

[0018] Preferably, the polyelectrolyte solution is a polydiallyldimethylammonium chloride (PDDA) solution with a concentration of 0.05-1 mol·L-1.

[0019] 3. Negative Charge Layer Deposition

[0020] S5. Montmorillonite, polyacrylic acid, and polyvinylidene fluoride are placed in a mortar in proportion and ground into powder with a diameter of less than 20 μm to achieve preliminary compounding of the above materials. The mixed powder is then poured into a crucible, and nitrogen methyl pyrrolidone is added. The mixture is stirred for 6-12 hours to prepare a slurry.

[0021] The mass ratio of the montmorillonite, polyacrylic acid, and polyvinylidene fluoride is 8:1:1. The amount of nitrogen methyl pyrrolidone added is determined by the mass of each portion, and the amount added per 1g of mixed powder is between 15-40mL.

[0022] In step S6, the base film treated in step S4 is immersed in the slurry prepared in step S5. Taking advantage of the negative charge of montmorillonite, the montmorillonite complex is electrostatically adsorbed as a functional layer to form a reed fiber / montmorillonite double-layer composite membrane. The composite membrane is dried in a conventional oven at 60-100°C for 12-24 hours, then transferred to a vacuum drying oven and dried for 12-24 hours at 60-120°C to obtain a dried composite membrane. Steps S4 and S6 can be repeated as needed to construct a multilayer composite membrane.

[0023] In the present invention, layer-by-layer self-assembly (LbL) technology utilizes the interaction between molecules to alternately deposit materials with opposite charges layer by layer on the substrate surface to form a multilayer film with a precisely controllable structure.

[0024] A self-assembled zinc ion battery composite membrane comprises a self-assembled catkin fiber layer and a montmorillonite composite layer. The catkin fiber layer has a thickness of about 600-1200 μm, and the montmorillonite composite layer has a thickness of about 50-200 μm.

[0025] Preferably, there is at least one montmorillonite composite layer.

[0026] Preferably, the montmorillonite composite layer comprises a mixed powder and nitrogen methyl pyrrolidone in a mass volume ratio of 1:(15-40), with the unit being g:mL, and the mixed powder comprises montmorillonite, polyacrylic acid and polyvinylidene fluoride in a mass ratio of 8:1:1.

[0027] Application of a layer-by-layer self-assembled zinc ion battery composite membrane in aqueous zinc ion batteries.

[0028] Application of a layer-by-layer self-assembled zinc ion battery composite separator in zinc ion symmetric batteries.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] 1. The reed fluff fiber used in the present invention is a natural fiber produced during the natural growth of reeds. It is inexpensive, environmentally friendly, highly flexible, and has strong water absorption capacity. The diaphragm made of it has good toughness, is not easy to break, and has a fine and uniform porous structure.

[0031] 2. Montmorillonite has a layered structure, good thermal stability, negative charge between layers, and can effectively adsorb Zn 2+ , and regulate Zn 2+ The transmission inside the diaphragm improves the ion transmission efficiency and inhibits the deposition and growth of zinc dendrites.

[0032] 3. The addition of polyacrylic acid and polyvinylidene fluoride membranes can adjust the hydrophilicity of the composite membrane and improve the mechanical properties of the membrane, reducing the damage of the negative electrode dendrites.

[0033] 4. The present invention utilizes LbL layer-by-layer self-assembly technology to prepare catkin fiber / montmorillonite composite membrane, wherein catkin fiber serves as the base membrane layer and montmorillonite composite serves as the functional layer. The prepared composite membrane has excellent ion transmission performance and good effect of inhibiting dendrite growth. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 It is a schematic diagram of the preparation process of the composite diaphragm in the present invention.

[0035] Figure 2 is a SEM image of the reed fiber base membrane prepared in Example 1;

[0036] Figure 3 is a SEM image of the reed fiber / montmorillonite composite membrane prepared in Example 1;

[0037] Figure 4 is the XRD pattern of the reed fiber / montmorillonite composite membrane prepared in Example 1;

[0038] Figure 5 1 is a schematic diagram of the assembly structure of the zinc ion symmetrical battery in Example 1;

[0039] Figure 6 The reed fiber / montmorillonite composite membrane prepared in Example 1 was used to assemble a zinc symmetrical battery. 2 , surface capacity 5mA·h / cm 2 Constant current charge and discharge curve measured at .

[0040] Figure 7The current density is (0.25-5-0.25) mA / cm 2 , with an area capacity of 1 mAh / cm 2 Under the conditions of , the rate performance of catkin fiber / montmorillonite composite membrane and Waterman glass fiber membrane GF / D was compared.

[0041] Figure 8 This is the SEM image of the surface of the negative electrode zinc sheet obtained by disassembling the battery after the same current density and test time. DETAILED DESCRIPTION

[0042] The present invention will be further described in detail below with reference to the accompanying drawings and specific examples. The following examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention.

[0043] Example 1

[0044] A method for preparing a layer-by-layer self-assembled zinc ion battery composite diaphragm comprises the following steps:

[0045] 1. Preparation of reed fiber base membrane

[0046] 1. Take 3.5g of cleaned reed fluff and put it into a 4% NaOH and 0.8% H2O2 aqueous solution system. Ultrasonic treatment is carried out for 15 minutes. Then, it is heated in a water bath at 80℃ for 2 hours to remove lignin. Then, the seed impurities are filtered out, washed with pure water three times, filtered again, and dried in an oven at 60℃ for 12 hours to obtain reed fluff fiber.

[0047] 2. Place the reed fiber in a mixed solution of 2.5 mol·L-1 KOH + 0.4 mol·L-1 Na2SO3 and hydrothermally react at 140°C for 12 hours to further remove lignin and hemicellulose;

[0048] 3. Wash the hydrothermally treated reed fiber with pure water for 3 times, adjust the pH value of the suspension to neutral, and use vacuum filtration technology to filter to form a wet film. Place the wet film between two pieces of glass and dry it in an oven at 60°C for 24 hours to obtain a reed fiber-based membrane with good toughness and uniform porous structure. The SEM image of its porous structure is shown in the figure below. Figure 2 shown.

[0049] Second, positive charge layer deposition

[0050] 4. Soak the reed catkin fiber-based membrane in a PDDA solution with a concentration of 0.05 mol·L-1 for 5 minutes to make its surface positively charged.

[0051] 3. Negative Charge Layer Deposition

[0052] 5. Take 8g of montmorillonite, 1g of polyacrylic acid, and 1g of polyvinylidene fluoride, put them into a mortar and grind them into fine powder to achieve preliminary compounding of the above materials. Then pour the mixed powder into a crucible, add 300mL of nitrogen methyl pyrrolidone, and stir for 6h to prepare a slurry with a negative charge.

[0053] 6. Immerse the positively charged base film into the slurry, and use the negatively charged property of montmorillonite to adsorb the montmorillonite composite functional layer through electrostatic action. Place the diaphragm in a conventional oven and dry it for 12 hours at 80°C, then transfer it to a vacuum drying oven and dry it for 12 hours at 100°C to obtain the following: Figure 1 The reed wool fiber / montmorillonite double-layer composite membrane shown.

[0054] The self-assembled zinc ion battery composite membrane obtained in this embodiment includes a self-assembled catkin fiber layer and a montmorillonite composite layer. The catkin fiber layer has a thickness of about 700 μm, and the montmorillonite composite layer has a thickness of about 80 μm.

[0055] This embodiment provides an application of a layer-by-layer self-assembled zinc ion battery composite membrane in an aqueous zinc ion battery.

[0056] This embodiment provides an application of a layer-by-layer self-assembled zinc ion battery composite separator in a zinc ion symmetrical battery.

[0057] The surface morphology SEM image of the composite diaphragm is as follows Figure 3 The XRD test results are shown in Figure 4 As shown, it can be seen that the composite membrane has obvious sharp characteristic peaks at 2θ = 6°, 19° and 27°, which are basically consistent with the characteristic peak positions of montmorillonite powder, indicating that the surface of the membrane has been covered by the montmorillonite functional layer.

[0058] 4. Symmetrical battery assembly

[0059] 7. Cut the reed fiber / montmorillonite double-layer composite membrane into 19mm diameter discs as the test cell membrane, 2mol / L ZnSO4 solution as the electrolyte, and zinc sheets as the positive and negative electrodes to assemble a zinc ion symmetrical battery for constant current charge and discharge test. The assembly structure of the zinc ion symmetrical battery is as follows: Figure 5 shown.

[0060] 5. Battery performance test

[0061] The assembled battery was tested with the CT3002A Blue Battery Test System for constant current charge and discharge and rate performance. During the constant current charge and discharge test, the higher the test current density, the faster the charge and discharge rate, the higher the electrochemical reaction rate, and the more it can reflect the stability of the battery under fast charge and discharge conditions. When the test current density is 10mA / cm 2, the surface capacity is 5mA·h / cm 2 When the battery using reed fiber / montmorillonite composite separator maintains stable cycle after 180 hours of charge and discharge cycle. Figure 6 .

[0062] At a current density of (0.25-5-0.25) mA / cm 2 , with an area capacity of 1 mAh / cm 2 Under the conditions of , the battery rate performance of the battery using the reed fiber / montmorillonite composite membrane and the battery using the Waterman glass fiber membrane GF / D was compared. The battery using the reed fiber / montmorillonite composite membrane has a lower polarization voltage, indicating that the zinc dendrite nucleation overpotential is larger and has a better effect of inhibiting zinc dendrite growth. The test results are shown in Figure 7 .

[0063] After completing the battery performance test at the same current density and the same time, the battery was disassembled, the negative zinc sheet was removed, and the surface morphology of the zinc sheet was observed using a scanning electron microscope. Figure 8 Compared with the battery using glass fiber separator ( Figure 8 a) Compared with the battery using reed fiber / montmorillonite composite membrane ( Figure 8 b) The zinc flakes are smoother and more complete, further confirming the inhibitory effect of catkin fiber / montmorillonite composite membrane on zinc dendrites.

[0064] Example 2

[0065] A method for preparing a layer-by-layer self-assembled zinc ion battery composite diaphragm comprises the following steps:

[0066] 1. Preparation of reed fiber base membrane

[0067] 1. Take 3g of cleaned reed fluff and put it into a 6% mass fraction of NaOH and 1.5% volume fraction of H2O2 aqueous solution system, ultrasonically treat it for 10 minutes, then heat it in a water bath at 60℃ for 4 hours to remove lignin, then filter out the seed impurities, wash it with pure water twice, filter it again, and dry it in an oven at 100℃ for 24 hours to obtain reed fluff fiber;

[0068] 2. Place the reed fiber in a mixed solution of 2.0 mol·L-1 KOH + 0.1 mol·L-1 Na2SO3 and perform a hydrothermal reaction at 120°C for 10 hours to further remove lignin and hemicellulose;

[0069] 3. Wash the hydrothermally treated reed fiber with pure water twice, adjust the pH value of the suspension to neutral, and use vacuum filtration technology to filter to form a wet film. Place the wet film between two pieces of glass and put it in an oven to dry at 100°C for 12 hours to obtain a reed fiber base membrane with good toughness and uniform porous structure.

[0070] Second, positive charge layer deposition

[0071] 4. Soak the reed catkin fiber-based membrane in a PDDA solution with a concentration of 1 mol·L-1 for 3 minutes to make its surface positively charged.

[0072] 3. Negative Charge Layer Deposition

[0073] 5. Take 8g of montmorillonite, 1g of polyacrylic acid, and 1g of polyvinylidene fluoride, put them into a mortar and grind them into fine powder to achieve preliminary compounding of the above materials. Then pour the mixed powder into a crucible, add 150mL of nitrogen methyl pyrrolidone, and stir for 12h to prepare a slurry with a negative charge.

[0074] 6. Immerse the above-mentioned positively charged base membrane in the slurry, and utilize the negatively charged property of montmorillonite to adsorb the montmorillonite composite functional layer through electrostatic action. Place the membrane in an ordinary oven and dry it for 24 hours at a temperature of 60°C. Then transfer it to a vacuum drying oven and dry it for 24 hours at a temperature of 120°C to obtain a catkin fiber / montmorillonite double-layer composite membrane.

[0075] 7. Soak the reed fiber / montmorillonite double-layer composite membrane in a 1 mol·L-1 PDDA solution for 3 minutes to make its surface positively charged.

[0076] 8. Immerse the double-layer composite membrane obtained in step 7 in the slurry, utilize the negative charge characteristic of montmorillonite to adsorb the montmorillonite composite functional layer through electrostatic action, place the membrane in an ordinary oven and dry it for 24 hours at a temperature of 60°C, and then transfer it to a vacuum drying oven and dry it for 24 hours at a temperature of 120°C to obtain a three-layer composite membrane of catkin fiber / montmorillonite / montmorillonite.

[0077] The self-assembled zinc ion battery composite membrane obtained in this embodiment includes a self-assembled catkin fiber layer and a montmorillonite composite layer. The catkin fiber layer is about 600 μm thick, and the montmorillonite composite layer is about 200 μm thick.

[0078] This embodiment provides an application of a layer-by-layer self-assembled zinc ion battery composite membrane in an aqueous zinc ion battery.

[0079] This embodiment provides an application of a layer-by-layer self-assembled zinc ion battery composite separator in a zinc ion symmetrical battery.

[0080] The battery using the reed fiber / montmorillonite / montmorillonite composite membrane of this embodiment still maintains stable cycling after 180 hours of charge and discharge cycles.

[0081] The reed fiber / montmorillonite / montmorillonite composite membrane of this embodiment has a lower polarization voltage, indicating that the zinc dendrite nucleation overpotential is larger and has a better effect of inhibiting the growth of zinc dendrites.

[0082] The zinc sheets of the battery using the catkin fiber / montmorillonite / montmorillonite composite separator of this embodiment are smoother and more complete, further confirming the inhibitory effect of the catkin fiber / montmorillonite / montmorillonite composite separator on zinc dendrites.

[0083] Example 3

[0084] A method for preparing a layer-by-layer self-assembled zinc ion battery composite diaphragm comprises the following steps:

[0085] 1. Preparation of reed fiber base membrane

[0086] 1. Take 10g of cleaned reed fluff and put it into an aqueous solution of 8% NaOH by mass and 1.0% H2O2 by volume. Ultrasonic treatment is performed for 20 minutes. Then, it is heated in a water bath at 70°C for 3 hours to remove lignin. Then, the seed impurities are filtered out, the mixture is washed with pure water 4 times, filtered again, and dried in an oven at 80°C for 18 hours to obtain reed fluff fiber.

[0087] 2. Place the reed fiber in a mixed solution of 4 mol·L-1 KOH + 1 mol·L-1 Na2SO3 and perform a hydrothermal reaction at 130°C for 15 hours to further remove lignin and hemicellulose;

[0088] 3. Wash the hydrothermally treated reed fiber with pure water three times, adjust the pH value of the suspension to neutral, and use vacuum filtration technology to filter to form a wet film. Place the wet film between two pieces of glass and put it in an oven to dry at 80°C for 18 hours to obtain a reed fiber base membrane with good toughness and uniform porous structure.

[0089] Second, positive charge layer deposition

[0090] 4. Soak the reed catkin fiber-based membrane in a 0.5 mol·L-1 PDDA solution for 10 minutes to make its surface positively charged.

[0091] 3. Negative Charge Layer Deposition

[0092] 5. Take 8g of montmorillonite, 1g of polyacrylic acid, and 1g of polyvinylidene fluoride, put them into a mortar and grind them into fine powder to achieve preliminary compounding of the above materials. Then pour the mixed powder into a crucible, add 400mL of nitrogen methyl pyrrolidone, and stir for 10h to prepare a slurry with a negative charge.

[0093] 6. Immerse the above-mentioned positively charged base membrane in the slurry, and utilize the negatively charged property of montmorillonite to adsorb the montmorillonite composite functional layer through electrostatic action. Place the membrane in an ordinary oven and dry it for 18 hours at a temperature of 100°C. Then transfer it to a vacuum drying oven and dry it for 18 hours at a temperature of 60°C to obtain a catkin fiber / montmorillonite double-layer composite membrane.

[0094] The self-assembled zinc ion battery composite membrane obtained in this embodiment includes a self-assembled catkin fiber layer and a montmorillonite composite layer. The catkin fiber layer has a thickness of about 1200 μm, and the montmorillonite composite layer has a thickness of about 50 μm.

[0095] This embodiment provides an application of a layer-by-layer self-assembled zinc ion battery composite membrane in an aqueous zinc ion battery.

[0096] This embodiment provides an application of a layer-by-layer self-assembled zinc ion battery composite separator in a zinc ion symmetrical battery.

[0097] The battery using the reed fiber / montmorillonite composite separator of this embodiment still maintains stable cycling after 180 hours of charge and discharge cycles.

[0098] The reed fiber / montmorillonite composite separator of this embodiment has a lower polarization voltage, indicating that the zinc dendrite nucleation overpotential is larger and has a better effect of inhibiting the growth of zinc dendrites.

[0099] The zinc sheets of the battery using the catkin fiber / montmorillonite composite separator of this embodiment are smoother and more complete, further confirming the inhibitory effect of the catkin fiber / montmorillonite composite separator on zinc dendrites.

[0100] Example 4

[0101] The only difference between this embodiment and embodiment 2 is that:

[0102] After completing step 8, do the following:

[0103] 9. Soak the three-layer composite membrane of catkin fiber / montmorillonite / montmorillonite in a PDDA solution with a concentration of 1 mol·L-1 for 3 minutes to make its surface positively charged.

[0104] 10. Immerse the three-layer composite membrane obtained in step 9 in the slurry, and utilize the negatively charged property of montmorillonite to adsorb the montmorillonite composite functional layer through electrostatic action. Place the membrane in an ordinary oven and dry it for 24 hours at a temperature of 60°C. Then transfer it to a vacuum drying oven and dry it for 24 hours at a temperature of 120°C to obtain a four-layer composite membrane of catkin fiber / montmorillonite / montmorillonite / montmorillonite.

[0105] The self-assembled zinc ion battery composite membrane obtained in this embodiment includes a self-assembled catkin fiber layer and a montmorillonite composite layer. The catkin fiber layer is about 600 μm thick, and the montmorillonite composite layer is about 200 μm thick.

[0106] The battery using the reed fiber / montmorillonite / montmorillonite / montmorillonite composite membrane of this embodiment still maintains stable cycling after 180 hours of charge and discharge cycles.

[0107] The reed fiber / montmorillonite / montmorillonite / montmorillonite composite membrane of this embodiment has a lower polarization voltage, indicating that the zinc dendrite nucleation overpotential is larger and has a better effect of inhibiting the growth of zinc dendrites.

[0108] The zinc sheets of the battery using the catkin fiber / montmorillonite / montmorillonite / montmorillonite composite separator of this embodiment are smoother and more complete, further confirming the inhibitory effect of the catkin fiber / montmorillonite / montmorillonite / montmorillonite composite separator on zinc dendrites.

[0109] It should be understood that in order to streamline the present disclosure and aid understanding of one or more of the various inventive aspects, in the above description of exemplary embodiments of the invention, various features of the invention are sometimes grouped together into a single embodiment, figure, or description thereof. However, this disclosed method should not be interpreted as reflecting an intention that the claimed invention requires more features than are expressly recited in each claim. Rather, as reflected in the claims, inventive aspects lie in less than all of the features of the previously disclosed embodiments. Accordingly, the claims that follow the detailed description are hereby expressly incorporated into this detailed description, with each claim standing on its own as a separate embodiment of the invention.

[0110] Although the present invention has been described with respect to a limited number of embodiments, it will be apparent to those skilled in the art, having benefit of the foregoing description, that other embodiments are contemplated within the scope of the invention thus described. Furthermore, it should be noted that the language used in this specification has been selected primarily for readability and didactic purposes, rather than for the purpose of explaining or limiting the subject matter of the present invention. Consequently, many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the appended claims. The disclosure of the present invention is intended to be illustrative rather than restrictive of the scope of the invention, which is defined by the appended claims.

[0111] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A layer-by-layer self-assembled zinc ion battery composite membrane, characterized in that: The invention comprises a self-assembled reed fiber layer and a montmorillonite composite layer.

2. The zinc ion battery composite diaphragm self-assembled layer by layer according to claim 1, characterized in that: There is at least one montmorillonite composite layer, the reed wool fiber layer has a thickness of 600-1200 μm, and the thickness of one montmorillonite composite layer has a thickness of 50-200 μm.

3. The layer-by-layer self-assembled zinc ion battery composite diaphragm according to claim 1, characterized in that: The montmorillonite composite layer includes mixed powder and nitrogen methyl pyrrolidone in a mass volume ratio of 1: (15-40), and the unit is g: mL. The mixed powder includes montmorillonite, polyacrylic acid and polyvinylidene fluoride in a mass ratio of 8:1:

1.

4. The method for preparing a layer-by-layer self-assembled zinc ion battery composite membrane according to any one of claims 1 to 3, characterized in that: The following steps are involved:

1. Preparation of reed fiber base membrane: S1, taking 3-10g of cleaned reed fluff, placing it in a 4-8% by mass NaOH, 0.8-1.5% by volume H2O2 aqueous solution system, ultrasonically treating it for 10-20 minutes, then heating it in a water bath at 60-80°C for 2-4 hours, filtering it to remove seed impurities, washing it with pure water several times, filtering it again, and drying it in an oven to obtain reed fluff fiber; S2, placing the reed fibers into a KOH / Na2SO3 mixed solution and subjecting them to a hydrothermal reaction at 120-140° C. for 10-15 hours; S3, washing the reed fibers after the hydrothermal treatment in S2 with pure water multiple times to obtain a suspension, adjusting the pH value of the suspension to neutral, and then filtering to form a wet film, placing the wet film between two pieces of glass, and drying it in an oven to obtain a reed fiber base film; Second, positive charge layer deposition: S4, soaking the reed catkin fiber-based membrane obtained in S3 in a positively charged polyelectrolyte solution for 3-10 minutes to make its surface positively charged; 3. Negative charge layer deposition: S5, grinding montmorillonite, polyacrylic acid, and polyvinylidene fluoride into powder in a mass ratio of 8:1:1 to obtain a mixed powder, then adding nitrogen methyl pyrrolidone to the mixed powder, with the amount of nitrogen methyl pyrrolidone added being between 15-40 mL per 1 g of the mixed powder, and stirring for 6-12 h to prepare a slurry; S6, immersing the reed fiber base membrane treated in S4 into the slurry prepared in S5 to form a reed fiber / montmorillonite double-layer composite membrane; placing the composite membrane in an oven to dry, and then transferring it to a vacuum drying oven to dry, thereby obtaining the membrane.

5. The preparation method according to claim 4, characterized in that After S6 is completed, S4 and S6 are repeated as needed to construct a multi-layer composite diaphragm.

6. The preparation method according to claim 4, characterized in that In S2, the KOH / Na2SO3 mixed solution is 2-4 mol·L-1KOH+0.1-1 mol·L-1Na2SO3.

7. The preparation method according to claim 4, characterized in that Dry in an oven at 60-100°C for 12-24 hours; dry in a vacuum drying oven at 60-120°C for 12-24 hours.

8. The preparation method according to claim 4, characterized in that In S4, the polyelectrolyte solution is a polydiallyldimethylammonium chloride (PDDA) solution with a concentration of 0.05-1 mol·L-1.

9. Use of the layer-by-layer self-assembled zinc ion battery composite membrane according to any one of claims 1 to 3 in aqueous zinc ion batteries.

10. Use of the layer-by-layer self-assembled zinc ion battery composite separator according to any one of claims 1 to 3 in a zinc ion symmetrical battery.